(x-a) (x-b) =0

If either (x-a)=0 or (x-b)=0 then the entire expression is equal to 0.

Set the first factor equal to 0 and solve.

(x-a) =0

x=a

Set the next factor equal to 0 and solve.

(x-b) =0

x=b

**The solution is all values that make (x-a)(x-b) =0 true.**

** ...**

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

(x-a) (x-b) =0

If either (x-a)=0 or (x-b)=0 then the entire expression is equal to 0.

Set the first factor equal to 0 and solve.

(x-a) =0

x=a

Set the next factor equal to 0 and solve.

(x-b) =0

x=b

**The solution is all values that make (x-a)(x-b) =0 true.**

**x= a, b **

**which in your problem is choice b) x=a, x=b**